2001
DOI: 10.1046/j.1365-3040.2001.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and metal sensitivity of vacuolar channels from the roots of the aquatic plant Eichhornia crassipes

Abstract: Using the patch-clamp technique, we investigated the transport properties of vacuolar ion channels from the roots of water hyacinth, Eichhornia crassipes (Mart. Solms, Pontederiacae). Eichhornia crassipes vacuoles displayed large voltage-dependent rectifying slow-vacuolar (SV) currents, which activated in a few seconds at positive potentials and deactivated at negative voltages in a few hundreds of millseconds. Similarly to SV channel previously identified in the tonoplast of terrestrial plants, SV currents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…membrane transporters) and/or facilitated diffusion (ion channels). Most of the reports dealing with lead transport are related to terrestrial plants (Sunkar et al 2000;Wang et al 2007) and little is known about floating aquatic plants (Paganetto et al 2001). Olguín et al (2005) have suggested that in S. minima, Pb 2+ is accumulated intracellularly through the use of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…membrane transporters) and/or facilitated diffusion (ion channels). Most of the reports dealing with lead transport are related to terrestrial plants (Sunkar et al 2000;Wang et al 2007) and little is known about floating aquatic plants (Paganetto et al 2001). Olguín et al (2005) have suggested that in S. minima, Pb 2+ is accumulated intracellularly through the use of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…, 1994; Dobrovinskaya et al. , 1999; Paganetto et al. , 2001; Schulz‐Lessdorf and Hedrich, 1995; Weiser et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different factors, such divalent cations (Pottosin et al 2001), polyamines (Dobrovinskaya et al 1999a(Dobrovinskaya et al , 1999b, and heavy metals (Paganetto et al 2001;Carpaneto 2003), control the ion flux through the open channel. Most studies have concentrated on the regulation of the SV channel by cytosolic factors.…”
Section: Introductionmentioning
confidence: 99%